1985-1986 ネン マクマードサウンド チイキ ノ コクサイ キョウドウ カンソク - 神沼, 克伊; カミヌマ, カツタダ; Kaminuma, Katsutada (1986)
P(論文) 1985-1986年のマクマードサウンド地域の国際共同観測は, 第6年目を迎えた「エレバス火山国際地震研究(IMESS)」のみを実施した。日本からは神沼克伊(国立極地研究所), 三浦哲(東北大学理学部), 山田守(名古屋大学理学部)の3名が参加した。3名のうち神沼はマクマード基地に, 三浦, 山田はスコット基地に滞在した。日本隊は例年通りテレメータ観測網の記録系の保守, 観測した磁気テープの再生, 地震記録の読み取りを行った。また, スコット基地からエレバス山頂の噴煙量も毎日調査した。ニュージーランド隊と共同で新しくバード山山頂, ロス島の東端のウィルソン岩小屋付近の2点で重力測定を実施した。さらに日本隊だけで, テラノバ山北方斜面他2点で新しく重力を測定し, エバンス岬他5点で再測をした。 Continuous seismic observations have been carried out since December 1980 by a cooperative International Mount Erebus Seismological Studies (IMESS) which includes Japan, the United States and New Zealand. Three Japanese participating in the IMESS visited the McMurdo Sound region during the 1985-1986 field season. They were K. KAMINUMA (Nationl Institute of Polar Research), S. MIURA (Faculty of Science, Tohoku University) and M. YAMADA (Faculty of Science, Nagoya University). KAMINUMA stayed at McMurdo Station and MIURA and YAMADA stayed at Scott Base. They conducted a series of scientific research programs during their tenure at McMurdo Station and Scott Base from 22 November 1985 to 6 January 1986. 1. Seismic observation by the telemetry network : Japanese scientists played back the seismic magnetic tapes which have recorded since February 1985. The daily frequencies of eruptions and volcanic earthquakes occurring in and around Mount Erebus were counted and earthquakes were scaled to determine their locations. 2. Plume observation : The volume of plume at the Erebus summit was watched from Scott Base. 3. Gravity : Two new gravity stations were established on Ross Island by the cooperation with Japan and New Zealand. Gravity was measured at eight other points on Ross Island during the 1985-1986 field season. departmental bulletin paper